Rediscovering the carotid pulse: unlocking hidden insights in the era of AI-driven healthcare - Ben-Pazi, Hilla; Jhashan, Shady; Salame, Haill; Cohen, Hillit; Matot, Idit; Pazi, Meron Ben; Kirma, Yaniv; Elmaliach, Lior; Lavi, Yair; Mintz, Pnina; Corvaja, Nicola; Dvir, Danny; et al. (Frontiers in Neurology, 2025)
From ancient Chinese medicine to medieval European practice, the carotid pulse has long been recognized as a vital window into vascular health. Yet in modern clinical medicine, this rich physiological signal has been largely overlooked. While artificial intelligence (AI) has transformed healthcare through advanced data interpretation, it has also inadvertently diverted focus from acquiring novel physiological data—particularly from the carotid artery. This review highlights the underutilized potential of carotid hemodynamics and explores how emerging sensor technologies, combined with AI, can transform stroke prevention, real-time cerebrovascular monitoring, and broader vascular care. As a central conduit between the heart and brain, the carotid artery conveys dynamic hemodynamic information relevant not only to neurology, but also to cardiology and pulmonary medicine. Recent advances in non-invasive, continuous monitoring now enable real-time assessment of vascular stiffness, pulse wave patterns, and early cerebrovascular compromise—capabilities that were previously inaccessible with traditional, intermittent evaluation methods. Focusing on the neurological context, this review outlines emerging opportunities in carotid monitoring, identifies key hemodynamic markers, and evaluates the clinical consequences of their underuse. By integrating AI with enhanced, continuous data acquisition from the carotid artery, the medical community may pursue new diagnostic and predictive pathways, advancing toward proactive, precision-based care and improved patient outcomes.